Trypanosoma cruzi PARP is enriched in the nucleolus and is present in a thread connecting nuclei during mitosis - Kevorkian, María Laura (2022)
Poly (ADP-ribose) polymerase (PARP) is responsible for the synthesis of ADP-ribose polymers, which are involved in a wide range of cellular processes such as preservation of genome integrity, DNA damage signaling and repair, molecular switches between distinct cell death pathways, and cell cycle progression. Previously, we demonstrated that the only PARP present in T. cruzi migrates to the nucleus upon genotoxic stimulus. In this work, we identify the N-terminal domain as being sufficient for TcPARP nuclear localization and describe for the first time that TcPARP is enriched in the parasite’s nucleolus. We also describe that TcPARP is present in a thread-like structure that connects two dividing nuclei and co-localizes with nucleolar material and microtubules. Furthermore, ADP-ribose polymers could also be detected in this thread during mitosis. These findings represent a first approach to new potential TcPARP functions inside the nucleus and will help understand its role well beyond the largely described DNA damage response protein in trypanosomatids.